Releasing upper Lapland : Martin Heidegger and the question concerning nature - Hast, Sanna (2008)
This study is a phenomenological-hermeneutical analysis of the Upper Lapland forest conflict. Reindeer husbandry, state forestry and nature-based tourism are the main sources of livelihood in Upper Lapland. Also large, state-owned wilderness areas have been reserved for nature conservation. Utilisation of the forests and wilderness areas for different purposes has lead to a situation where the livelihoods are forced to compete with each other and conflicts between the different interest groups have arisen during recent years.